Testing long-run neutrality of money: evidence from Malaysian stock market - Puah, Chin-Hong; Muzafar Shah, Habibullah; Lim, Kian−Ping (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This paper presents the empirical evidence on the long-run neutrality (LRN) of money in the stock market in Malaysia using seasonal adjusted monthly data from 1978:1 to 1999:12 based on the bivariate ARIMA framework developed by Fisher and Seater (1993). Besides the main stock index, the sectoral stocks indexes also have been tested by different measurements of money supply, namely M1, M2, and M3. Generally, the findings support the LRN of money in Malaysia’s stock market and the results are robust to the sensitivity tests of different monetary aggregates. This would imply that the permanent stochastic changes in money supply do not have influential effect towards the real stock returns in Malaysia.